FESTIVAL ERAU SEBAGAI KEARIFAN LOKAL BUDAYA MASYARAKAT ADAT KUTAI KARTA NEGARA DAN PERKEMBANGANNYA DI ERA MODERN SAAT INI - Aulia Vivi Yulianingrum, Sadam Kholik, Linda Setia Ningsih, Arman (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The Erau Festival, as a cultural celebration of the Kutai Kartanegara traditional community, is a real manifestation of local wisdom passed down from generation to generation. This article aims to present an overview of the Erau Festival as a manifestation of local wisdom and how this festival has adapted to the modern era. This research uses a journal-based literature method involving analysis, synthesis and interpretation of information found in scientific journals, as well as some electronic information obtained. The brief results of this research are that the Erau tradition is a tradition that has existed for a long time but is still developing to this day by continuing to be carried out every year on Kutai Kartanegara's birthday, which is packaged by the regional government in the form of a cultural festival. Currently, Erau has transformed into a multi-event, a harmonious collaboration between traditions that are still well maintained and a dynamic contemporary atmosphere. So that in this increasingly modern era, Erau as the local wisdom of Kutai Kartanegara can still be preserved as a cultural event that has distinctive characteristics, character and a strong attraction for tourists, both local and foreign tourists. The efforts above are a way for local governments to preserve culture.